Fin-de-Siècle Fictions, 1890s-1990s - Mousoutzanis, A. author. aut Link
IX, 258 p.
Keywords: Fin-de-Siècle Fictions, 1890s- 1990s focuses on fin-de-siècle British and postmodern American fictions of apocalypse and investigates the ways in which these narratives demonstrate shifts in the relations among modern discourses of power and knowledge.